Monetary and fiscal policies in times of large debt: Unity is strength - Francesco Bianchi; Renato Faccini; Leonardo Melosi (Danmarks Nationalbank, 2021)
We build and estimate a novel TANK model with partially unfunded debt to study whether the record high debt-to-GDP ratio threatens US inflation stability. In response to business cycle shocks, the monetary authority controls inflation, and the fiscal authority stabilizes debt. The central bank accommodates unfunded fiscal shocks, causing persistent movements in inflation and real interest rates, leading to a fiscal theory of trend inflation. Fiscal trend inflation accounts for the bulk of inflation dynamics. The current situation is in line with historical experience. Unfunded shocks sustain the recovery and cause a temporary inflation increase that counteracts deationary non-policy shocks.
Keywords: E50; E62; E30; 330; Monetary policy; Public finances; fiscal policy